FORMAÇÃO CONTINUADA E IDENTIDADE DOCENTE: UM ESTUDO SOBRE O PROGRAMA DE DESENVOLVIMENTO EDUCACIONAL MUNICIPAL EM UNIÃO DA VITÓRIA - Mazur, Marcela (2021)
This dissertation discusses the Municipal Educational Development Program (PDEM) of União da Vitória, which is characterized as a continuing education program offered by the Municipal Department of Education for basic education teachers. The program was a partnership between the Municipal Department of Education and the State University of Paraná – UNESPAR, campus of União da Vitória. The training included the participation of forty-two teachers from the Municipal Teaching Staff. The general objective of the work was to understand in which ways the PDEM interfered in the teaching identity of the teachers who participated in the program, understanding that recording the formative experience of the PDEM and its meanings can produce properly pedagogical contributions on the teaching profession in all its scientific and complex complexity. human. The study was developed from an anthropological and sociological perspective, considering both the interpretive intentionality from the perspective of subjects and culture, as well as the resulting aspects of the social structure in which they are inserted. The use of concepts about culture and identity, school culture and teacher identity helped to overcome an individualistic and personal view of the uniqueness of PDEM teachers, seeking a more comprehensive understanding of their actions and choices in the process of continuing education. Data for research were obtained in the second half of 2019, by reading documents relevant to the program, materials produced during training, and a questionnaire with open questions in order to better understand the behavior of the teachers. The research results indicated that the PDEM is effective as a socializing formative instance that enabled the redefinition of educational practices. Bearing in mind the perspective of Nóvoa (1995) – that the teaching identity focuses more on the exercise of the profession, as if the teacher were their own practice – and based on the study of the meanings that basic education teachers produced about the PDEM, it is possible to see that PDEM interfered in the teaching identity of those who participated in the program, having direct effects on classroom practice, through learning and exchange of experiences.